2011
DOI: 10.1002/mrm.23266
|View full text |Cite
|
Sign up to set email alerts
|

Detection of osteoarthritis in knee and hip joints by fast field‐cycling NMR

Abstract: It is known that in the early stages of osteoarthritis, the concentration of glycan proteins decreases in articular cartilage. This phenomenon is under active research to develop a means to characterize osteoarthritis accurately in the early stages of the disease, when still reversible. However, no method of quantification has yet shown clear success in this area. In this article, we propose a novel approach to detect glycan depletion using fast field-cycling NMR. This technique was previously reported to allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 23 publications
1
46
1
Order By: Relevance
“…In these studies, a proportionality between the Q‐peak area and the protein concentration was confirmed. Recently, this finding was efficiently exploited for an early‐stage detection of osteoarthritis in articular cartilage ex vivo , of which initialization is associated with a depletion of glycosaminoglycan from the tissue extracellular matrix. In dry‐cured hams, water molecules are depleted from the tissue, which affects the water/protein content.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, a proportionality between the Q‐peak area and the protein concentration was confirmed. Recently, this finding was efficiently exploited for an early‐stage detection of osteoarthritis in articular cartilage ex vivo , of which initialization is associated with a depletion of glycosaminoglycan from the tissue extracellular matrix. In dry‐cured hams, water molecules are depleted from the tissue, which affects the water/protein content.…”
Section: Discussionmentioning
confidence: 99%
“…The FFC technique is not uniquely suitable for such a type of research; one can envisage T 1 distribution measurements performed on a low‐field MRI scanner equipped with a permanent magnet. The advantage of the FFC relaxometry over the steady‐field relaxometry is that it introduces through varying B 0 the second dimension that can be exploited in a complementary way or in its own right to monitor the OA‐induced changes in cartilage . Thus, attempts were made to analyze quasi‐continuous T 1 dispersion profiles before and after trypsin digestion in terms of elementary Bloembergen‐Purcell‐Pound–type relaxation processes with individual correlation times.…”
Section: Discussionmentioning
confidence: 99%
“…The MRI techniques developed for early diagnosis of OA exploit spatially resolved measurements of T 1 , T 2 , and T 1ρ as potential biomarkers, thanks to their correlation with the composition and structure of AC . In addition to the MRI mapping of T 1 and T 2 , fast field‐cycling (FFC) NMR relaxometry has recently been used in the attempt to correlate the biological state of AC cartilage with T 1 dispersion . The FFC experiments were carried out in the magnetic fields B 0 = 0.2 mT to 470 mT, which span quadrupolar relaxation enhancement (QRE) peaks.…”
Section: Introductionmentioning
confidence: 89%
“…FFC‐MR relaxometry is an approach to directly measure NMR relaxation properties . FFC‐MRI combines the techniques of field‐cycling nuclear MR relaxometry with the imaging methods of MRI, offering access to biological information not available from conventional imaging at a fixed field strength .…”
Section: Introductionmentioning
confidence: 99%